FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DI KABUPATEN KUNINGAN - Amir Hamzah; Nani Sumarni; Sani Rahmasari (Program Studi Akuntansi, Universitas Kuningan, 2023)
This study aims to analyze the effect of tax knowledge and tax penalties on taxpayer compliance in Kuningan Regency. Data were obtained from 150 respondents using a questionnaire that had been tested for validity and reliability. Multiple linear regression analysis was used to test the hypothesis. The results showed that tax knowledge and tax penalties significantly influence taxpayer compliance. This indicates the importance of tax knowledge and penalty policies in improving taxpayer compliance.Keywords: Tax Knowledge, Tax Penalties, Taxpayer Compliance, Taxpayers, Kuningan Regency.